Study on the visual perception of magazine cover designs in the journal “Reto” during the periods 2012-2021 - Aranguren-Corredor, Julián Felipe
This article describes the results of a mixed-method research conducted in the first semester of 2023 at the Centro de Gestión de Mercados, Logística y Tecnologías de Información (CGMLTI) of Sena Regional Distrito Capital, focusing on the visual perception generated by the graphic design of the magazine covers of “Reto” starting from 2020, within the academic community. Two instruments, one quantitative and one qualitative, were designed to collect data and information from the participants for each of the eight covers between the years 2012 and 2021. The analysis of quantitative data and interpretation of qualitative information generally indicate that the changes in illustrations and artistic style of the magazine had a positive impact in 2020.